Naringin Prevents Cognitive Dysfunction in Aging Rats by Inhibiting Toll-Like Receptor 4 (TLR4)/NF-κB Pathway and Endoplasmic Reticulum Stress. (21st February 2023) - Dai, Xiao-jie; Jia, Yi; Cao, Rui; Zhou, Mei-ning
Abstract : Objective . Naringin is a flavonoid derived from Chinese herbs. According to earlier studies, naringin may have the potential to alleviate aging-induced cognitive dysfunction. Therefore, this study attempted to explore the protective effect and underlying mechanism of naringin on aging rats with cognitive dysfunction. Methods . After the construction of a model of aging rats with cognitive dysfunction through subcutaneous injection of D-galactose (D-gal; 150 mg/kg), intragastric administration of naringin (100 mg/kg) was performed for treatment. Behavioral tests, including Morris water maze test (MWM), novel object recognition test (NORT), and fear conditioning test, were used to measure the cognitive function; ELISA and biochemical tests were used to determine the levels of interleukin (IL)-1 β, IL-6, monocyte chemoattractant protein-1 (MCP-1), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), malondialdehyde (MDA), and glutathione peroxidase (GSH-Px) in the hippocampus of rats in each group, respectively; H&E staining was used to observe the pathological changes in the hippocampus; Western blot was used to examine the expression of toll-like receptor 4 (TLR4)/NF- κ B pathway-related proteins and endoplasmic reticulum (ER) stress-related proteins in the hippocampus. Results . The model was successfully constructed by subcutaneous injection of D-gal (150 mg/kg). The behavioral test results showed that naringin could ameliorate the cognitive dysfunction and alleviate the histopathological damage of hippocampus. Moreover, naringin significantly improve the inflammatory response (the levels of IL-1 β, IL-6, and MCP-1 were decreased), oxidative stress response (MDA level was increased while GSH-Px activity was decreased), and ER stress (the expression of glucose-regulated protein 78 (GRP78), C/-EBP homologous protein (CHOP), and transcription factor 6 (ATF6) expression was downregulated), and increased the levels of neurotrophic factors BDNF and NGF in D-gal rats. Besides, further mechanistic studies revealed the downregulation of naringin on TLR4/NF- κ B pathway activity. Conclusion . Naringin may inhibit inflammatory response, oxidative stress, and ER stress by downregulating TLR4/NF- κ B pathway activity, thereby improving cognitive dysfunction and alleviating histopathological damage of hippocampus in aging rats. Briefly, naringin is an effective drug for the treatment of cognitive dysfunction.